2017
DOI: 10.2337/cd16-0020
|View full text |Cite|
|
Sign up to set email alerts
|

Stigma in People With Type 1 or Type 2 Diabetes

Abstract: IN BRIEF This study quantitatively measures diabetes stigma and its associated psychosocial impact in a large population of U.S. patients with type 1 or type 2 diabetes using an online survey sent to 12,000 people with diabetes. A majority of respondents with type 1 (76%) or type 2 (52%) diabetes reported that diabetes comes with stigma. Perceptions of stigma were significantly higher among respondents with type 1 diabetes than among those with type 2 diabetes, with the highest rate in parents of children with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

15
182
2
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 207 publications
(234 citation statements)
references
References 31 publications
15
182
2
2
Order By: Relevance
“…10 Stigma of patients with chronic depression has been reported to be due to a sense of shame, fear, lack of trust, lack of close relationships, and lack of communication. 11 In patients with type 2 diabetes, the disease creates negative images and internalizes itself as stigma. 12 The current study also found similar results, showing that the stigma of patients with type 1 diabetes was due to a sense of shame, fear, lack of trust, and lack of relationship.…”
Section: Limit Social Lifementioning
confidence: 99%
“…10 Stigma of patients with chronic depression has been reported to be due to a sense of shame, fear, lack of trust, lack of close relationships, and lack of communication. 11 In patients with type 2 diabetes, the disease creates negative images and internalizes itself as stigma. 12 The current study also found similar results, showing that the stigma of patients with type 1 diabetes was due to a sense of shame, fear, lack of trust, and lack of relationship.…”
Section: Limit Social Lifementioning
confidence: 99%
“…Some of the challenges of living with T1DM (e.g., disruptiveness, judgment, blame, shame), may be reflective of dimensions of the stigma surrounding T1DM, a phenomenon increasingly recognized among individuals with T1DM (Browne, Ventura, Mosely, & Speight, 2014; Dickinson, 2018; Liu et al, 2017). Many of the adolescent participants reported feeling uncomfortable at times when information about their T1DM was disclosed in social situations.…”
Section: Discussionmentioning
confidence: 99%
“…Stigma and negative experiences with type 2 diabetes can alter feelings of self-worth and lead to internalized stigma ( 16 ). Internalized stigma then can lead to fewer self-care behaviors, treatment nonadherence, difficulties with meaningful social interactions, and social isolation ( 14 , 16 ). When patients develop a negative relationship with their diabetes, they may change how they behave in public, try to hide the disease, have a lower sense of self-worth, and internalize stigma ( 16 ).…”
Section: Discussionmentioning
confidence: 99%
“…Considering the role that lifestyle plays in the management of diabetes, stigma may be influencing how people view the disease and, in turn, how the disease is treated. Diabetes stigma refers to negative feelings, such as exclusion, rejection, or blame, associated with having diabetes ( 14 ). The most common diabetes stigma, regardless of type of diabetes, was the perception that people with diabetes were responsible for developing their diabetes ( 14 ).…”
mentioning
confidence: 99%
See 1 more Smart Citation